A moving grid finite element method for the simulation of pattern generation by Turing models on growing domains - Madzvamuse, A; Maini, P; Wathen, A (2005)
Numerical techniques for moving meshes are many and varied. In this paper we present a novel application of a moving grid finite element method applied to biological problems related to pattern formation where the mesh movement is prescribed through a specific definition to mimic the growth that is observed in nature. Through the use of a moving grid finite element technique, we present numerical computational results illustrating how period doubling behaviour occurs as the domain doubles in size.